Data‐driven analysis of simultaneous EEG/fMRI reveals neurophysiological phenotypes of impulse control. Issue 9 (2nd May 2016) - Schmüser, Lena; Sebastian, Alexandra; Mobascher, Arian; Lieb, Klaus; Feige, Bernd; Tüscher, Oliver
Abstract: Response inhibition is the ability to suppress inadequate but prepotent or ongoing response tendencies. A fronto‐striatal network is involved in these processes. Between‐subject differences in the intra‐individual variability have been suggested to constitute a key to pathological processes underlying impulse control disorders. Single‐trial EEG/fMRI analysis allows to increase sensitivity for inter‐individual differences by incorporating intra‐individual variability. Thirty‐eight healthy subjects performed a visual Go/Nogo task during simultaneous EEG/fMRI. Of 38 healthy subjects, 21 subjects reliably showed Nogo‐related ICs (Nogo‐IC‐positive) while 17 subjects (Nogo‐IC‐negative) did not. Comparing both groups revealed differences on various levels: On trait level, Nogo‐IC‐negative subjects scored higher on questionnaires regarding attention deficit/hyperactivity disorder; on a behavioral level, they displayed slower response times (RT) and higher intra‐individual RT variability while both groups did not differ in their inhibitory performance. On the neurophysiological level, Nogo‐IC‐negative subjects showed a hyperactivation of left inferior frontal cortex/insula and left putamen as well as significantly reduced P3 amplitudes. Thus, a data‐driven approach for IC classification and the resulting presence or absence of early Nogo‐specific ICs as criterion for group selection revealed group differences at behavioral and neurophysiological levels. This may indicate electrophysiological phenotypes characterized by inter‐individual variations of neural and behavioral correlates of impulse control. We demonstrated that the inter‐individual difference in an electrophysiological correlate of response inhibition is correlated with distinct, potentially compensatory neural activity. This may suggest the existence of electrophysiologically dissociable phenotypes of behavioral and neural motor response inhibition with the Nogo‐IC‐positive phenotype possibly providing protection against impulsivity‐related dysfunction. Hum Brain Mapp 37:3114–3136, 2016 . ©2016 Wiley Periodicals, Inc .